Preferential Zn(2+) influx through Ca(2+)-permeable AMPA/kainate channels triggers prolonged mitochondrial superoxide production - Sensi, Stefano L. (The National Academy of Sciences, 1999)
Synaptically released Zn(2+) can enter and cause injury to postsynaptic neurons. Microfluorimetric studies using the Zn(2+)-sensitive probe, Newport green, examined levels of [Zn(2+)](i) attained in cultured cortical neurons on exposure to N-methyl-d-asparte, kainate, or high K(+) (to activate voltage-sensitive Ca(2+) channels) in the presence of 300 μM Zn(2+). Indicating particularly high permeability through Ca(2+)-permeable α-amino3-hydroxy-5-methyl-4-isoxazolepropionic-acid/kainate (Ca-A/K) channels, micromolar [Zn(2+)](i) rises were observed only after kainate exposures and only in neurons expressing these channels [Ca-A/K(+) neurons]. Further studies using the oxidation-sensitive dye, hydroethidine, revealed Zn(2+)-dependent reactive oxygen species (ROS) generation that paralleled the [Zn(2+)](i) rises, with rapid oxidation observed only in the case of Zn(2+) entry through Ca-A/K channels. Indicating a mitochondrial source of this ROS generation, hydroethidine oxidation was inhibited by the mitochondrial electron transport blocker, rotenone. Additional evidence for a direct interaction between Zn(2+) and mitochondria was provided by the observation that the Zn(2+) entry through Ca-A/K channels triggered rapid mitochondrial depolarization, as assessed by using the potential-sensitive dye tetramethylrhodamine ethylester. Whereas Ca(2+) influx through Ca-A/K channels also triggers ROS production, the [Zn(2+)](i) rises and subsequent ROS production are of more prolonged duration.